# Solve for c 4(2-c)+1=3(c+3) 4(2-c)+1=3(c+3)
Simplify 4(2-c)+1.
Simplify each term.
Apply the distributive property.
4⋅2+4(-c)+1=3(c+3)
Multiply 4 by 2.
8+4(-c)+1=3(c+3)
Multiply -1 by 4.
8-4c+1=3(c+3)
8-4c+1=3(c+3)
Add 8 and 1.
-4c+9=3(c+3)
-4c+9=3(c+3)
Simplify 3(c+3).
Apply the distributive property.
-4c+9=3c+3⋅3
Multiply 3 by 3.
-4c+9=3c+9
-4c+9=3c+9
Move all terms containing c to the left side of the equation.
Subtract 3c from both sides of the equation.
-4c+9-3c=9
Subtract 3c from -4c.
-7c+9=9
-7c+9=9
Move all terms not containing c to the right side of the equation.
Subtract 9 from both sides of the equation.
-7c=9-9
Subtract 9 from 9.
-7c=0
-7c=0
Divide each term by -7 and simplify.
Divide each term in -7c=0 by -7.
-7c-7=0-7
Cancel the common factor of -7.
Cancel the common factor.
-7c-7=0-7
Divide c by 1.
c=0-7
c=0-7
Divide 0 by -7.
c=0
c=0
Solve for c 4(2-c)+1=3(c+3)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top